2022
DOI: 10.1111/aji.13586
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0060551 promotes the migration and invasion of cervical cancer by upregulating TPD52

Abstract: Problem Cervical cancer has been recognized as the second most common cancer in women worldwide. Previous studies have reported that some circular RNAs (circRNAs) can influence the progression of cervical cancer. However, more researches are still required to unveil the underlying mechanism of how circRNAs regulate the progression of such cancer. We aimed at unveiling the mechanism of how circ_0060551 effected the progression of cervical cancer. Method of study RT‐qPCR and western blot assays were used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Among the family members (TPD52, TPD53, TPD54, and TPD55), TPD52 has been extensively studied due to its involvement in the malignancy of different cancer cells 50 . Numerous studies have demonstrated the upregulation of TPD52 at both the mRNA and protein levels in several cancers, including lung cancer 31 , 51 , 52 . In our study, we confirmed that TPD52 indeed acts as an oncogene and is regulated by the AR/circ-SLCO1B7/miR-139-5p signaling pathway, promoting lung cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Among the family members (TPD52, TPD53, TPD54, and TPD55), TPD52 has been extensively studied due to its involvement in the malignancy of different cancer cells 50 . Numerous studies have demonstrated the upregulation of TPD52 at both the mRNA and protein levels in several cancers, including lung cancer 31 , 51 , 52 . In our study, we confirmed that TPD52 indeed acts as an oncogene and is regulated by the AR/circ-SLCO1B7/miR-139-5p signaling pathway, promoting lung cancer progression.…”
Section: Discussionmentioning
confidence: 99%